2019
DOI: 10.1007/s11657-019-0607-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hip fracture on health-related quality of life and activities of daily living: the SPARE-HIP prospective cohort study

Abstract: Purpose The medical morbidity and mortality associated with neck of femur fractures is well-documented, whereas there is limited data for patient-reported outcomes. The aim of this study was to characterize the impact of neck of femur fractures on activities of daily living and patient-reported health-related quality of life. Methods Design and participants: Multicentric prospective cohort study. Consecutive sample patients with fragility hip fracture over 50 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In any case, these recent papers criticized the usefulness of vitamin D supplementation with the goal to maintain or improve musculoskeletal health in the general population, but its role in patients receiving treatment for osteoporosis is an entirely different topic. It is well-known that, in these patients, adequate calcium and vitamin D intake are essential, and their deficiency represents the most common reason for lack of response to any treatment, 5,8,9 This observation has been confirmed also in a recent large retrospective study based on Italian administrative databases. 4 The study showed once again that pharmacological treatments for osteoporosis are associated with a lower risk for both refracture and all-cause mortality to a greater extent when they are administered in combination with calcium and vitamin D. 4…”
Section: Requirements For Therapymentioning
confidence: 71%
See 2 more Smart Citations
“…In any case, these recent papers criticized the usefulness of vitamin D supplementation with the goal to maintain or improve musculoskeletal health in the general population, but its role in patients receiving treatment for osteoporosis is an entirely different topic. It is well-known that, in these patients, adequate calcium and vitamin D intake are essential, and their deficiency represents the most common reason for lack of response to any treatment, 5,8,9 This observation has been confirmed also in a recent large retrospective study based on Italian administrative databases. 4 The study showed once again that pharmacological treatments for osteoporosis are associated with a lower risk for both refracture and all-cause mortality to a greater extent when they are administered in combination with calcium and vitamin D. 4…”
Section: Requirements For Therapymentioning
confidence: 71%
“…4 Their recovery is usually slow and often incomplete. 5 For these reasons, a large proportion of fractured individuals is destined to lose function and independence and to suffer from persistent pain and decreased quality of life. 5 Due to the progressive aging of the general population, the annual incidence of fragility fractures is expected to rise from 3.5 million in 2010 to 4.5 million in 2025.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intertrochanteric fracture is a common osteoporotic fracture among elderly populations in an aging society [1][2][3]. Multiple comorbidities result in high rates of morbidity and mortality, which makes intertrochanteric fractures challenging to treat for orthopedic surgeons [4][5][6]. Early surgical xation on these aging patients has been proposed recently for early rehabilitation and has had a positive impact on reducing comorbidities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The lag screw tip position in the femoral head was classi ed by the Cleveland index (Figure 2a) [22]. 5. Femoral neck shortening: The femoral neck shortening distance was measured between the last follow-up and the immediate postoperative radiographs with the correction of the true implant diameters.…”
mentioning
confidence: 99%